International conference “phenomenological perspectives on cultural change and environmental challenges” - Kvašinskaitė, Rimantė (Creativity Studies, 2013)
On September 22–24, in 2011, the second international phenomenological conference took place in Vilnius, Lithuania. It was organized together with Antioch University of the USA and it was hosted in Vilnius Gediminas Technical University's Faculty of Architecture. Urbanists, philosophers, educators and other academic scholars had a chance to deepen their knowledge and present the results of their researches on the subject of “Phenomenological Perspectives on Cultural Change and Environmental Challenges”. More than 10 speakers from various countries had presented their speeches and afterwards actively indulged in group discussions on the most problematic issues. Due to a huge success that the event has proven to be, it is expected to be just a beginning of a new tradition to hold such conferences in the university regularly.Socialinių pokyčių ir aplinkos iššūkių fenomenologinės perspektyvosSantrauka. Antroji tarptautinė fenomenologų konferencija Lietuvoje įvyko 2011 m. rugsėjo 22–24 d. Ši konferencija, kitaip nei 2009 m. įvykusi jos pirmtakė, buvo organizuota kartu su JAV Antiocho universitetu. Vilniaus Gedimino technikos universitete, Architektūros rūmuose urbanistai ir architektai turėjo galimybę sužinoti daug naujo ir patys pateikti savo tyrimų rezultatus tema ,,Socialinių pokyčių ir aplinkos iššūkių fenomenologinės perspektyvos“. Daugiau nei 10 pranešėjų iš viso pasaulio parengė kalbas ir po jų aktyviai įsitraukė į diskusijas, kuriose buvo gvildenami problematiškiausi klausimai. Tikėtina, kad tokios konferencijos ateityje taip pat bus organzijuojamos ir pamažu virs pasididžiavimo verta tradicija.Reikšminiai žodžiai: fenomenologija, socialiniai pokyčiai, aplinkos iššūkiai.First Published Online: 28 Jun 2013